EFFECT OF NaCI ON THE GERMINATION, SEEDLING AND SOME METABOLIC CHANGES IN SWEET BASIL (OCIMUM BASILICUM) - ZIDAN, M.A.; ZAHRANI, H.S. AL- (Biological Sciences - PJSIR, 2022)
The effect of different salinity levels (up to 120 mM NaCl) on germination, Seedling growth, dry matter and some related metabolic parameters of sweet basil tOcimum basilicumi was studied. During germination it tolerated salinity up to 60 mM NaCI. However, seedling growth and dry matter production were decreased by NaCI greater than 40 mM NaCI. Soluble carbohydrate and proline concentration of seedling increased with increase of salinity. However, soluble protein and amino acids were decreased by salinity. In long term (36 days) experiment, growth decreased with increasing salinity levels, except at 5 and 10mM NaCl where growth was increased. Water content in the whole test plant increased at 5 mM NaCI and decreased as salinity increased to 50 mM NaCI. These results may lead to the conclusion that, sweet basil is a medium tolerant crop and is considered as glycophyte.